The Anti-Russian Strategy of Germany in the Caucasus in the Years of World War I - I I Barinov (RUDN Journal of Russian History, 2013)
The article is devoted to the study and critical analysis of the strategic plans of Germany against Russia in the Caucasus region during the I World War. The paper aims to identify the basic characteristics of German strategy and the reasons for its failure. It is also possible to trace the specific relationship of social and national conflicts in the Caucasus of early 20 th century.